The Impact of Body Mass Index Upon the Efficacy of Adalimumab in Hidradenitis Suppurativa - Frew, John W.; Singh, N.; Jiang, C. S.; Vaughan, R.; Krueger, J. G. (Frontiers in Medicine, 2021)
Elevated BMI in Hidradenitis Suppurativa is associated with decreased response to Adalimumab therapy. BMI is proposed to segregate distinct disease subtypes. It remains unresolved whether a threshold BMI exists above which increased dosages may provide clinical benefit. Individual patient data from 578 PIONEER Phase 3 participants were analyzed. Descriptive, multivariable regression analysis and receiver operating characteristic (ROC) curves were calculated to assess the relationship between BMI and clinical outcome measures using R v3.5.3. Participants in the overweight and obese BMI category had reduced odds (58% and 67% respectively) of achieving HiSCR (OR=0.42 (95%CI -0.19,0.91) p=0.03), (OR=0.33 (95%CI 0.16,0.67) p=0.002) compared to participants with BMI<25. Reduction in AN count and IHS4 score was not significantly associated. ROC analysis did not reveal any cut off value predictive of treatment outcome. No correlation between BMI and baseline disease activity or covariate interactions were identified. These findings suggest BMI is a significant covariate in the setting of lower baseline disease activity, supporting the concept of disease heterogeneity and differential therapeutic response to Adalimumab.